Lactate regulators contribute to tumor microenvironment and predict prognosis in lung adenocarcinoma - Shang, Shipeng; Wang, Mi-zhou; Xing, Zhiyuan; He, Ningning; Li, Shangyong (Frontiers in Immunology, 2022)
Lactic acid, as a product of glycolysis, increased tumor cell migration and invasion in tumor microenvironment. Besides, Lactic acid promotes the expression of programmed death-1 expression (PD-1) in regulatory T cells, which could improve the treatment effect PD-1 blockade therapy. However, the implications of lactic acid in tumor microenvironment of lung adenocarcinoma (LUAD) remain largely unknown. We evaluated the relationship DNA methylation and the mutation frequency of lactate regulators and found the low mutation frequency of lactate regulators the factors occurred in TCGA-LUAD cohort, except TP53. Lactate regulators were significantly associated with immune cells and the expression of LDHA was positively correlated with percentage of CD4 T cell, CD8 T cell, M1 macrophages and multiple immune pathways. In addition, two clusters were defined using lactate regulators and LDHA was significantly up-regulated in clutser1 which had a poor overall survival. Lactate signature (LaSig) was constructed based on 25 key signatures using LASSO regression algorithm, which had a good performance in predicting survival and immunotherapy response in LUAD. Moreover, high LaSig group had a higher sensitivity to Cisplatin, Erlotinib, Gemcitabine and Vinblastine. In conclusion, the study of Lactate regulators in lung adenocarcinoma can deepen our understanding of tumor microenvironment and guide personalized treatment.